Regarding "Burden of Comorbidities and Healthcare Resource Utilization Among Medicaid-Enrolled Extremely Premature Infants" - Ava Tsapatsaris; Miran Bhima; Tejas C. Sekhar (Journal of Health Economics and Outcomes Research)
In their article, Mowitz et al investigated the burden of comorbidities and healthcare resource utilization among extremely premature infants enrolled in Medicaid, laying a foundation for further policy action.